2012
DOI: 10.1152/ajpheart.00011.2012
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of TRPV1-mediated coupling of coronary blood flow to cardiac metabolism in diabetic mice: role of nitric oxide and BK channels

Abstract: channel-dependent coronary function is compromised in pigs with metabolic syndrome (MetS). However, the mechanisms through which TRPV1 channels couple coronary blood flow to metabolism are not fully understood. We employed mice lacking TRPV1 [TRPV1 (Ϫ/Ϫ) ], db/db diabetic, and control C57BKS/J mice to determine the extent to which TRPV1 channels modulate coronary function and contribute to vascular dysfunction in diabetic cardiomyopathy. Animals were subjected to in vivo infusion of the TRPV1 agonist capsai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…TRP channels, as Ca 2+ -permeable channels, play a beneficial role in cardiovascular diseases. Moreover, the TRPV1 channel has been included in the activation of eNOS in several previous studies (40)(41)(42)(43). The present study demonstrated that TRPV1 overexpression increased the phosphorylation of eNOS in the myocardium from isoproterenol-treated mice.…”
Section: Discussionsupporting
confidence: 69%
“…TRP channels, as Ca 2+ -permeable channels, play a beneficial role in cardiovascular diseases. Moreover, the TRPV1 channel has been included in the activation of eNOS in several previous studies (40)(41)(42)(43). The present study demonstrated that TRPV1 overexpression increased the phosphorylation of eNOS in the myocardium from isoproterenol-treated mice.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, previous vasoreactivity studies in isolated pressurized mouse coronary microvessels revealed a capsaicin-dependent relaxation that was impaired in db/db mice compared with controls 13 . Several mechanisms that mediate CAP-induced vasodilation have been proposed.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…ACCEPTED MANUSCRIPT 13 pretreated with L-NAME at CAP concentrations of 10 -7~1 0 -5 mol/L (P < 0.05, Fig. 3A),…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…18 This parallels mast cell induction of cardiac hypertrophy and cardiac fibrosis, 19 with mast cell knockout impacting repair responses in infarcted hearts. 20 From a neuronal and excitable tissue perspective the literature identifies TRPV1 as a molecular sensor to detect tissue ischemia, 21 as responsible for excitation of cardiac nocioceptors by bradykinin, 22 coupling myocardial blood flow to cardiac metabolism, 23 and regulating vascular tension. 24 TRPV1 is therefore putatively involved in both immunological and neuronal, and producing left ventricular hypertrophy by constriction of the aorta.…”
Section: Discussionmentioning
confidence: 99%